2018
DOI: 10.1115/1.4040581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impurities on Compressor and Cooler in Supercritical CO2 Cycles

Abstract: With the increasing demand for electric power, the development of new power generation technologies is gaining increased attention. The supercritical carbon dioxide (S-CO2) cycle is one such technology, which has relatively high efficiency, compactness, and potentially could provide complete carbon capture. The S-CO2 cycle technology is adaptable for almost all of the existing heat sources such as solar, geothermal, fossil, nuclear power plants, and waste heat recovery systems. However, it is known that optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…However, due to the fact that T c is different for various mixtures, this assumption will cause the performance comparison of mixtures under different compressor inlet temperatures. (2) For the work of Vesely et al [24,25] and Guo et al [23], the range of employed gas fraction is too less. Although Baik and Lee [22] considered the whole fraction range 0-1, most of the employed additives belong to organic fluids, which may decompose in the high temperature.…”
Section: Current Status Of Co 2 -Based Mixturesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the fact that T c is different for various mixtures, this assumption will cause the performance comparison of mixtures under different compressor inlet temperatures. (2) For the work of Vesely et al [24,25] and Guo et al [23], the range of employed gas fraction is too less. Although Baik and Lee [22] considered the whole fraction range 0-1, most of the employed additives belong to organic fluids, which may decompose in the high temperature.…”
Section: Current Status Of Co 2 -Based Mixturesmentioning
confidence: 99%
“…They found that all researched mixtures except CO 2 -H 2 S had negative effects on the cycle efficiency and net power output. Thereafter, they examined the effect of different impurity compositions on the performance of various cycle components at different inlet temperatures of main compressor [25]. The above studies on the Brayton cycle with CO 2 -based mixtures are summarized in Table 1.…”
Section: Current Status Of Co 2 -Based Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Valencia et al (2020), in their study on the influence of mixtures, concludes that there are two groups: mixtures that decrease the critical temperature (s-CO2/He, s-CO2/Kr, s-CO2/CH4 y s-CO2/C2H6) and mixtures that increase the critical temperature (s-CO2/COS, s-CO2/H2S, s-CO2/NH3, s-CO2/SO2, s-CO2/C5H10, s-CO2/C5H12), among others. So far, several studies have been conducted to discuss the feasibility and performance of the CO2-based supercritical mixtures power cycle [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Running this described system at supercritical conditions can further cut costs and increase efficiency as the combined oxy-methane, with higher density supercritical CO2 diluent (sCO2), requires less pumping power for the same power output, while running with high power output comparable to conventional cycles (see refs. [2][3][4][5][6][7] for sCO2 power cycles).…”
Section: Introductionmentioning
confidence: 99%